Processing of RNA Containing 8-Oxo-7,8-Dihydroguanosine (8-oxoG) by the Exoribonuclease Xrn-1 - Cheyenne N. Phillips (Frontiers Media S.A., 2021)
Understanding how oxidatively damaged RNA is handled intracellularly is of relevance due to the link between oxidized RNA and the progression/development of some diseases as well as aging. Among the ribonucleases responsible for the decay of modified (chemically or naturally) RNA is the exonuclease Xrn-1, a processive enzyme that catalyzes the hydrolysis of 5′-phosphorylated RNA in a 5′→3′ direction. We set out to explore the reactivity of this exonuclease towards oligonucleotides (ONs, 20-nt to 30-nt long) of RNA containing 8-oxo-7,8-dihydroguanosine (8-oxoG), obtained via solid-phase synthesis. The results show that Xrn-1 stalled at sites containing 8-oxoG, evidenced by the presence of a slower moving band (via electrophoretic analyses) than that observed for the canonical analogue. The observed fragment(s) were characterized via PAGE and MALDI-TOF to confirm that the oligonucleotide fragment(s) contained a 5′-phosphorylated 8-oxoG. Furthermore, the yields for this stalling varied from app. 5–30% with 8-oxoG located at different positions and in different sequences. To gain a better understanding of the decreased nuclease efficiency, we probed: 1) H-bonding and spatial constraints; 2) anti-syn conformational changes; 3) concentration of divalent cation; and 4) secondary structure. This was carried out by introducing methylated or brominated purines (m1G, m6,6A, or 8-BrG), probing varying [Mg2+], and using circular dichroism (CD) to explore the formation of structured RNA. It was determined that spatial constraints imposed by conformational changes around the glycosidic bond may be partially responsible for stalling, however, the results do not fully explain some of the observed higher stalling yields. We hypothesize that altered π-π stacking along with induced H-bonding interactions between 8-oxoG and residues within the binding site may also play a role in the decreased Xrn-1 efficiency. Overall, these observations suggest that other factors, yet to be discovered/established, are likely to contribute to the decay of oxidized RNA. In addition, Xrn-1 degraded RNA containing m1G, and stalled mildly at sites where it encountered m6,6A, or 8-BrG, which is of particular interest given that the former two are naturally occurring modifications.